Role of Government Authorities in Land Acquisition and For Rehabilitation of Land Owners: Balancing public interest and landowners' rights in government land acquisition (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The general public opinion on the purchasing of property is unfavorable when the government acquires land on behalf of the private sector, whose primary aim is to increase benefit. In comparison, citizens too accommodating of government procurement, as the public-sector project is seen to improve the wellbeing of society as a whole and not that of any private citizen or community. Traditionally, the government (defense, railways, etc. or public sector corporations have acquired the bulk of the property.[1] With liberalization, both utilities and manufacturing have been more privatized and private demand for property has risen. The Land Acquisition Act represents a constitutional declaration of the authority of the State to exert eminent jurisdiction over the land on its territories. It denies the individual from whom the property has been bought the ability to select whether or not to split the land as long as the purchase has been made public.[2] The theory of eminent fields is intricately related to creation and maintenance. Eminent domain in its sense of designation implies the State's right to seize private property for a public reason. The purpose of the compensation varies from appropriation to purchase. This doctrine is part of the Land Acquisition Act 1894 and has over the years established jurisprudence around the texts and use of legislation which privileges the power of the State while rendering it more or less prone to legal challenges.[3]Throughout the evolution of civilization, cultures have struggled to reconcile constitutional freedom with State control. The government's acquisition of land has risen with rising demand on land due to urbanization, rapid economic growth, increasing infrastructure needs, etc. in particular in a fast-growing economy like India. The Indian government has confiscated the property of individuals for the greatest good and development reasons, which ensures that millions of citizens are displaced.[4] At the international level it is viewed as a breach of human rights but land acquisition is a question of time, and the only thing that can render acquisition operation smooth without resistance is to strike a balance that is, land acquisition must serve the object of public interest or welfare on the one side and landowners' rights to rehabilitate and resettle on the other. The position of the Indian government in this respect is highly appreciable as it has implemented some policies and legislation.